Switzerland : Financial System Stability Assessment. (IMF Staff Country Reports; Country Report, 2019)
Swiss financial institutions are well capitalized and could withstand the severe shocks under the adverse stress test scenarios, but macrofinancial vulnerabilities are deepening. Important reforms have been made since the 2014 FSAP, but several critical recommendations and emerging challenges have yet to be fully addressed. Capital buffers have increased across all categories of banks, and while the two global systemically important banks have downsized and deleveraged significantly since the global financial crisis, since 2013 they have been growing again. Macroprudential measures have not been taken since 2014 and is constrained by having only one mandated tool and a self-regulation agreement with banks. The financial supervisor (FINMA) has developed into a trusted supervisor, but as a small entity, it relies heavily on external auditors to conduct on-site supervision; the associated conflict of interest and supervisory objectivity risks need to be carefully managed. The combination of an ex-post funding mechanism, a low cap on banks' contributions, and a private deposit insurance agency run by active bankers, weakens the crisis management arrangements.